Long‐Term Open‐Label Safety Study of Rizatriptan Acute Treatment in Pediatric Migraineurs. Issue 1 (18th October 2012) - Hewitt, David J.; Pearlman, Eric; Hämäläinen, Mirja; Lewis, Donald; Connor, Kathryn M.; Michelson, David; Ceesay, Paulette; Assaid, Christopher; Bachman, Robert; Harper Mozley, Lyn; Dupre, Nicole; Strickler, Nancy; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the safety/tolerability of rizatriptan in the long‐term acute treatment of migraine in pediatric patients. Background Acute migraine treatment options for children are limited. A recent single‐attack trial demonstrated that rizatriptan is effective in eliminating migraine headache pain in this population. We evaluated the long‐term safety and efficacy of rizatriptan when used for intermittent acute treatment. Methods Open‐label study in pediatric migraineurs ages 12‐17 years. Patients weighing <40 kg received rizatriptan (orally disintegrating tablet) 5 mg, and those weighing ≥40 kg received 10 mg. Patients could treat up to 8 mild/moderate/severe migraine attacks per month for up to 12 months. One dose of study medication was allowed in a 24‐hour period. Results A total of 674 patients were enrolled, and 606 patients were treated with study medication (N = 583 for 10 mg, N = 23 for 5 mg). The mean duration in the study was 292 days, and the mean number of doses of study medication taken was 20. Over the course of the study within 14 days post‐any‐dose, 66.0% (400) of the 606 treated patients had any adverse event, 2.3% (14) discontinued due to an adverse event, 2.6% (16) had a serious adverse event, and 23.4% (142) had a triptan‐related adverse event. Of the 16 patients with serious adverse events within 14 days post‐any‐dose, the adverse events in 3 were considered drug‐related; all 3 patient's adverse events were classified as serious only because they were associated with an overdose (use of >1 dose of study medication in a 24‐hour period). The mean percentage of patient's attacks with pain freedom at 2‐hours post‐dose was 46.3%; this was relatively consistent over time (Months 1‐3 = 43.7%, Months 4‐6 = 51.9%, Months 7‐9 = 49.9%, Months 10‐12 = 49.5%). Conclusion Rizatriptan was generally safe and well tolerated in the long‐term acute treatment of migraine in pediatric patients aged 12‐17 years and demonstrated a consistent treatment effect over time.